THE INFLUENCE OF DISCIPLINE ON THE PERFORMANCE OF MAKASSAR CITY REGIONAL REVENUE AGENCY EMPLOYEES - Sudarmi, Sudarmi; Ranteta’dung , Rilfan Kasi’; Syam, Jumiati; Yasni, Yasni; Tobeoto , Kristison (SEAN Institute, 2023)
The aim of this research is to determine how discipline influences employee performance at the Makassar City Regional Revenue Agency. This type of research is quantitative, with a total sample of 35 employees in the advertising sector of the Regional Revenue Agency of Makassar City. The data collection techniques used in this research were observation, interviews and questionnaires. The method used is simple linear regression analysis with the help of SPSS 16. The results of this research show that the t test (partial) for the Discipline variable (X) produces a probability value (sig) = 0.000 < 0.05, so discipline has a positive and significant interaction with Employee performance (Y) at the Makassar City Regional Revenue Agency, with a regression coefficient value of 0.484 and a probability value (sig) of 0.000. And R Square is 0.962 or 96.2%, which means that the performance of employees at the Makassar City Regional Revenue Agency is influenced by discipline.